Evaluation of selective cyclooxygenase‐2 inhibitor‐induced small bowel injury: Randomized cross‐over study compared with loxoprofen in healthy subjects. Issue 3 (25th September 2012) - Mizukami, Kazuhiro; Murakami, Kazunari; Yamauchi, Mika; Matsunari, Osamu; Ogawa, Ryo; Nakagawa, Yoshifumi; Okimoto, Tadayoshi; Kodama, Masaaki; Fujioka, Toshio
Abstract : Aim: Non‐steroidal anti‐inflammatory drugs have the potential to injure the mucosa of the upper digestive tract and small bowel, whereas celecoxib (a selective cyclooxygenase‐2 inhibitor) has less influence on the entire digestive tract mucosa. The present study was conducted to compare the extents of small bowel mucosal injury induced by celecoxib and loxoprofen (the most frequently used non‐steroidal anti‐inflammatory drugs in Japan). Methods: Ten healthy adult males were given celecoxib (200 mg/day, Group C) and loxoprofen (180 mg/day, Group L) in a cross‐over design for 14 days, and the influence of each drug on small bowel mucosa was evaluated by comparing pre‐ and post‐treatment capsule endoscopy findings. We measured the percentage of patients with small bowel mucosal injury following administration of these drugs as primary endpoint. Additionally, mean number of small bowel mucosal injuries per subject was analyzed as secondary endpoint. Results: The percentage of subjects experiencing small bowel mucosal injury as primary endpoint was 10% in Group C and 70% in Group L after treatment. This magnitude of the difference of between Group C and Group L was statistically significant ( P  = 0.031). The number of small bowel mucosal injuries as secondary endpoint differed significantly between the two groups, and the influence of celecoxib on small bowel injury was less than that of loxoprofen. Conclusion: These results indicate that celecoxib has less influence on small bowel mucosa than loxoprofen and can be used safely.